Padrões de distribuição, modelagem, conservação e diversidade micromorfológica foliar de espécies de Solanum subg. Leptostemonum (Solanaceae) - Sampaio, Valéria da Silva (2019)
In order to understand the species distribution pattern, the influence of environmental variables on the distribution and the leaf micromorphological diversity of plants occurring in the neotropics, representatives of Solanum subg. Leptostemonum (Solanaceae) were selected. Solanum is characterized by species with significant economic importance, with recognized diversity, richness and endemism in the Neotropical region, in addition to high leaf morphological plasticity. The present study had as objectives 1) to elucidate the current distribution pattern of Solanum section Erythrotrichum, identifying the richness, diversity and environmental variables that influence the distribution of the taxa from the modeling, 2) to elaborate model of environmental suitability of a new species with for conservation purposes, 3) to relate the morphological pattern of leaf trichomes to the distribution patterns and vegetation types where the species occur, and 4) to describe the morphology and histochemistry of the first record of the petiolar gland in Solanum. For that, occurrence data were obtained from field collections, visits to national/international herbarium, specialized literature and analysis of collections available online. The environmental variables were obtained from Wordclim. The distribution models were developed in the program R. The leaf micromorphological diversity was analyzed using usual techniques in anatomy and scanning electron microscopy. The section Erythrotrichum is exclusively neotropical, with 25 species distributed in seven domains, 25 provinces, with eight distribution patterns. The richness of the domains are Paraná and Chaco, and the Atlântica, Caatinga and Floresta do Paraná provinces. Brazil has the greatest wealth, diversity and endemism, in addition to new records and species in danger of extinction. The environmental variables with the greatest contribution to species distribution were the Mean Diurnal Range, Temperature Seasonality and Mean Temperature of Wettest Quarter. A new species of restricted distribution was identified and the potential distribution model for conservation purposes was elaborated, indicating new areas of occurrence. The leaf micromorphological diversity is represented by a diversity of trichomes, which do not correspond to the distribution patterns and vegetation types, in addition to highlighting the first record of secretory structure in the Solanum petiole. Therefore, a broader distribution pattern than that currently known for section Erythrotrichum was observed, many of them with few records, threatened and poorly collected, with a high micromorphological diversity of leaf trichomes. In addition to the discovery of a new species and morphological novelties in the genus Solanum.